Identification of transient phenomena occurring at the initiation and termination of wheelset sliding - Lata, Michael; Voltr, Petr (Transport, 2012)
The paper deals with adhesion experiments on an actual traction vehicle. An efficient and quite simple method was employed to detect dynamical effects occurring at the exceeding of the adhesion limit. Along with the disabled anti-slip protection system, the examined wheelset was repeatedly brought into gross sliding while acceleration was measured taking the selected components of the running gear. The experiment confirmed the assumption that the initiation and termination of sliding were accompanied by intense dynamical effects which, additionally, could be precisely identified.First Published Online: 30 Mar 2012